'"Perfect ladies" are seldom interesting': locating modernity in Irene Dunne's early stardom. Issue 4 (2nd October 2022) - McKay, Ciara
Abstract : This article examines the early career of Irene Dunne (1898-1990). I argue that by reconstructing her stardom using film analysis alongside contemporary newspapers and magazines, we can greatly enrich discourse surrounding the star, situating her as a feminist figure. Contemporary publicity reveals that, although often situated as a quasi-Victorian lady, Dunne's independent personality, ambition, and unconventional marriage were emphasised to fans. Indeed, both Dunne's onscreen characters and press coverage often stressed modernity, validating working women and 'companionate marriage'. In investigating the duality of this messaging, which presented Dunne as conventionally 'feminine' and as a career woman, I argue that her image expanded contemporary conceptions of femininity. Her engagement with taboo themes such as divorce and adultery is also explored, and placed in the context of Dunne's own Catholicism, as well as increasing film censorship. Ultimately, I claim that her importance within the film studies academy has been under-stated to date, arguing that her 'ladylike'-ness, modernity, and strong religious faith combine to form a unique stardom.